Growth Parameters for Films of Hydrothermally Synthesized One-Dimensional Nanocrystals of Zinc Oxide - Mohammad A. Mahmood; Sadaqat Jan; Ibrar A. Shah; Imran Khan (International Journal of Photoenergy)
Zinc oxide has been the focus of material research due to its potential applications in a variety of novel fields. The material exhibits anisotropic growth in the form of single crystal rods/wires of length in microns and thickness in several tens of nanometers through a facile and low temperature hydrothermal route wherein size, morphology, orientation, and growth rate are strongly dependent on a number of synthesis parameters. In this review article we intend to present/discuss the effects of important growth parameters of zinc oxide that have been reported in the literature. These parameters include concentration of the precursor solution, growth time, role of hexamine, synthesis temperature, pH of the precursor, and seeding layer deposited on a substrate.